Comparison of energy acted on workpiece among Twin-body Plasma Arc Welding, Non-transferred Plasma Arc Welding and Plasma Arc Welding. (October 2016) - Zhang, Ruiying; Jiang, Fan; Chen, Shujun
Abstract: A novel welding process named Twin-body Plasma Arc Welding (TPAW) is proposed in this paper. The main arc in TPAW is established between tungsten electrode and guide electrode. In comparison with Non-transferred Plasma Arc Welding (NPAW) where one of the arc terminal is the nozzle, the workpieces are both not connected into the circuit loop, and the energy loss is less than that of NPAW. In comparison with Plasma Arc Welding (PAW) where one of the arc terminal is the workpiece, the nozzles are both not connected into the main arc circuits, and the anode effects are not worked on the workpieces. To examine the energy of these arcs by an intuitive way, a series of experimental system were designed and stagnation ablation experiments were conducted on Gr. D steel workpieces. The ablation regions which characterize the energy received by the workpiece are observed, measured and analyzed. It is found that the diameter of ablation region (i.e., the energy received by the workpieces) from TPAW is smaller than that of PAW, but is much larger than that of NPAW, as increasing the welding current and plasma gas flow rate. The welds by TPAW have smaller MZ area and smaller HAZ area but similar penetration in comparison with those by PAW, the ones by NPAW could not observe MZ or HAZ under the same parameters, indicating that the total heat input distribution of TPAW is smaller than that of PAW and much larger than that of NPAW. This tendency provides a possible method to better control the energy of plasma arc and expand the application of plasma arc.